SOME MISINTERPRETATIONS IN TRANSLATING LAW ARTICLES FROM ENGLISH TO INDONESIA AND INDONESIA TO ENGLISH (A case study at the fourth semester faculty of law) - Ardiyan Ardiyan (Pujangga: Jurnal Bahasa dan Sastra, 2016)
AbstractThe article will discuss some misinterpretations while the learning process in the classroom in translating the 1st Newspaper from English to Indonesia and Indonesia to English. andThe Jakarta post The purpose of the study is to identify, examine, and explain somemisinterpretations encountered by students in translating the article of law in the 1 timeNewspaper from English into Indonesia and Indonesia into English, while the learningprocess was happening in the classroom, especially fourth semester faculty of law. Theconclusions can be grouped into two categories such as: the nature of the source – languagetext to the target of the language and the student‘s lack of knowledge about the grammar.Keywords: Learning process, the grammar, the nature of the source-language, targetlanguagest